LATE QUATERNARY FAUNAL CHANGES IN NORTH-EASTERN PATAGONIA (ARGENTINA) ACCORDING TO A DYNAMIC MOSAIC OF BENTHIC HABITATS: TAPHONOMIC AND PALEOECOLOGICAL ANALYSES OF MOLLUSK ASSEMBLAGES -- Preprint doi:10.5710/AMGH.24.08.2016.2961 (Ameghiniana, 2016)
The aim of this study was to describe and interpret the paleoenvironmental history of the San Matías Gulf (SMG) in northern Patagonia, Argentina, associated to possible biotic and abiotic changes occurred during the late Quaternary. In this regard a taphonomic (disarticulation, right/left valve ratio; fragmentation, abrasion, teeth preservation) and paleoecologic (alpha diversity, species abundance, life habit, substrate preference, feeding mode) analysis of A. purputata (the target species) and its accompanying faunal remains (the non-target species) in modern, Holocene and Pleistocene shell assemblages was performed. The general trend of the SMG throughout the late Quaternary is as a low energy environment, with varying intensity depending on the study area. Additionally, each study site contains different substrates showing patches of sand and rock, and this would also have determined the presence of certain species; in turn, the proportion of sandy and rocky patches may have changed over time which led to the development of different local paleocommunities. This gulf therefore presents a dynamic mosaic of environments over time, as evidenced by taphonomic and paleoecological analyses. Its waters would have been sufficiently rich in nutrients to allow the development of the filter fauna which have dominated the late Quaternary, especially A. purpurata. Dual feeder gastropods from hard substrates (Crepidula species) have increased in proportion through the Holocene. The variation in the composition of the fauna accompanying A. purpurata is due to certain physical, biological and even anthropic environmental conditions, which have changed through time. These changes coincided with the Last Glacial Maximum, the final configuration of the SMG and the Climatic Optimum of the Holocene.